Analysis of Recent Research Trends in Thread Embedding Acupuncture for Low Back Pain - Yae Gi Min; Hyang Gi Lim; Hyun Jong Lee; Jung Hee Lee; Sung Chul Lim; Yun Kyu Lee; Jae Soo Kim (MEDrang Inc., 2024)
This study aimed to provide the basis of treatment effects by analyzing randomized control trials (RCTs) on the use of thread embedding acupuncture (TEA) for low back pain that were published between February 2018 and July 2023. In total, 2,865 articles were retrieved from international and Korean databases. Nine of these articles were selected and evaluated based on the following categories: (1) year of publication, (2) type of disease, (3) sample size, (4) treatment interventions, (5) treatment frequency and duration, (6) insertion point and depth of thread embedding, (7) types and sizes of threads and needles, (8) evaluation indexes, (9) treatment outcomes, and (10) side effects. The risk of bias in RCTs was also assessed. This study also emphasizes the importance of further research on TEA for clinical treatment and the use of objective approaches. Furthermore, detailed method descriptions and results are important in determining the efficacy of TEA.